Stable N,N’-diarylated dihydrodiazaacene radical cations - Xie, Gaozhan; Bojanowski, Maximilian; Brosius, Victor; Wiesner, Thomas; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemistry - a European journal, 2021)
Three stable N,N’-diarylated dihydroazaacene radical cations were prepared by oxidation of neutral N,N’-diarylated dihydroazaacenes synthesized via palladium-catalyzed Buchwald-Hartwig aminations of aryl iodides with N,N’-dihydroazaacenes. Both neutral as well as oxidized species were investigated via UV-vis spectroscopy, single crystal analysis, and DFT calculations. All the radical cations are surprisingly stable—their absorption spectra in dichloromethane remain unchanged in ambient conditions for at least 24 hours.